Sakofa: Evaluating Zakat Microfinance Program - Rakhmawati - (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
Zakat microfinance (ZMF) is an alternative to the limitation of zakat institution and microfinance institution in empowerment program. To make sure the zakat microfinance is on the track and to boost its performance and its benefit, evaluation is needed. This study aims to do an operational evaluation of productive zakat program formed in the micro-economic empowerment program named Sakofa (Madrasah Ekonomi Dhuafa/ School for Economics of the Poor) of Dompet Dhuafa Yogyakarta. Primary data were gathered from Sakofa beneficiaries in Sleman, Bantul, and Gunung Kidul. The findings show that all monetary aspects are better after running the program. Using ADePT software, headcount index, poverty gap, poverty severity, Watts index, and the average time taken to exit poverty are lower after doing the program. Altruism and saving behavior are better after Sakofa Program is implemented. Unfortunately, mustahiq were lack of discipline and desire to be independent. The effectiveness of counseling material on religiosity is the lowest. In short, Sakofa Program has a good performance in improving their prosperity.Â Keywords: productive zakat, zakat microfinance, poverty alleviation, empowerment, poverty index